Sustainable, regional, developed? «Sustainability» as a model for rural regions the example of Pyhrn-Eisenwurzen, Austria - Maier, Andreas (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
The first section of this article deals with the concept of “sustainability” and examines the broader conditions affecting strategies to bring about sustainable regional development. Part Two extends the discussion to include the two lead projects undertaken in the Pyhrn-Eisenwurzen region of Austria— the “Kalkalpen National Park” and the State Exhibition entitled “Land of the Hammers”. Part Three draws on the product-cycle model in an attempt to identify potential breaks with the trends of development found in Pyhrn-Eisenwurzen. The article concludes by presenting some general conclusions regarding the status and prospects of a policy of sustainable regional development in Europe.
Keywords: Article